Magic Seeds - Naipaul, V. S. (New York Alfred A. Knopf, 2004)
Willie Chandran feels as though the life he lives is not his own. But his listlessness washes away in a flood of encouragement from his radically political sister. Inspired, he joins an underground liberation movement in India. But after years of revolution and incarceration, he grows disillusioned and returns to England, still hoping to find his true self.
Keywords: Revolutionaries -- India -- Social reformers